Heterogeneity and Tension Between Different Ways of Understanding Development. An Anthropological Study of Coexistence Between Forestry Companies and Mapuche Communities in the Araucanía Region of Chile - Noelia Carrasco Henríquez (CUHSO)
This paper presents key research findings about the relationshipbetween forestry companies and Mapuche communities in Chile, from theperspective of anthropological studies of development, adressed during theFondecyt proyect 11080196. Methodologically, the research is the result ofintensive and extensive ethnographic approach on the dynamics and relationalprocesses between the actors, during the 2008-2011 period. Interviews,participant observation and document analysis were the main strategiesused. The main results higlight that both sector —forestry companies andthe Mapuche communities— has its own internal diversity, trends and tensions,that impact the overall social relations quality in the territory of LaAraucania, which is historically and socially marked by cultural and economicgaps. The research allowed to see that in this context, the relationshipbetween forestry companies and the Mapuche community reflects contactsbetween different logics —ie. modes, styles, value systems, practices andperformed knowledges, relating to the environment, development and theeconomy. These contacts —sociologically understood as social relations—are flexible, but always within a range of inequalities that undermine communities